Timing and imaging evidence in sport: Objectivity, intervention, and the limits of technology - Finn, J. (Journal of Sport and Social Issues, 2016)
This article analyzes timing and imaging systems used as sports decision aids (SDAs). Evidence of athletic performance in the form of timing and imaging data is the product of distinct interactions between humans, technology, and the live environment. As such, sports decisions are fallible. Yet the measurement of athletic performance is often presented as irrefutable thanks to enhanced technological precision. As this article shows, there are limits to the accuracy of timing and imaging systems as they are deployed in the physical environment, but such limits are rarely acknowledged in the public and professional discourse surrounding elite-level sport. To address this issue, the article analyses three sporting decisions: the 100 m butterfly race between Michael Phelps and Milorad Cavic at the 2008 Beijing Olympics; the third-place tie between Jeneba Tarmoh and Alysson Felix at the 2012 U.S. Olympic Trials; and the gold medal tie between skiers Tina Maze and Dominique Gisin at the 2014 Olympic games. The article examines the professional and public discourse surrounding each event as well as the regulations governing timing and imaging data in each sport to stress the situatedness and fallibility of SDAs. The article identifies limits to the accuracy of timing and imaging systems as they are deployed in the physical environment and calls on sports regulating bodies to clearly articulate the capabilities and limitations of timing and imaging systems in the production of evidence.